2002
DOI: 10.1046/j.0022-3042.2001.00009.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione decreases in dopaminergic PC12 cells interfere
with the ubiquitin protein degradation pathway: relevance 
for Parkinson's disease?

Abstract: Parkinson's disease (PD) is characterized by the presence of proteinaceous neuronal inclusions called Lewy bodies in susceptible dopaminergic midbrain neurons. Inhibition of the ubiquitin-proteasome protein degradation pathway may contribute to protein build-up and subsequent cell death. Ubiquitin is normally activated for transfer to substrate proteins by interaction with the E1 ubiquitin ligase enzyme via a thiol ester bond. Parkinson's disease is also characterized by decreases in midbrain levels of total g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 44 publications
(49 reference statements)
1
45
0
Order By: Relevance
“…Although neuronal death associated with decreased glutathione content cannot be blocked by competitive or noncompetitive glutamate receptor antagonists, it can be effectively circumvented by treatment with the antioxidants vitamin E and idebenone (14). Glutathione depletion and hypofunction of glutathione-dependent antioxidant enzymes have been linked directly to the pathogenesis of stroke (15), Huntington's disease (16,17), and Parkinson's disease (18)(19)(20)(21) in studies of rodent models as well as human autopsy tissue.…”
mentioning
confidence: 99%
“…Although neuronal death associated with decreased glutathione content cannot be blocked by competitive or noncompetitive glutamate receptor antagonists, it can be effectively circumvented by treatment with the antioxidants vitamin E and idebenone (14). Glutathione depletion and hypofunction of glutathione-dependent antioxidant enzymes have been linked directly to the pathogenesis of stroke (15), Huntington's disease (16,17), and Parkinson's disease (18)(19)(20)(21) in studies of rodent models as well as human autopsy tissue.…”
mentioning
confidence: 99%
“…Polyubiquitin is added to proteins targeted for UPS degradation by a series of ligases (E1, E2, and E3 ligases). Dithiocarbamates can lead to GSH oxidation (27), and GSH depletion results in the loss of E1 ligase activity (14). Ziram does not appear to act by lowering GSH, because depleting cellular GSH using buthionine sulfoximine (1 mM) had no effect on UPS activity, and ziram did not alter the amount of reduced GSH in the cells at concentrations up to 50 M (data not shown).…”
Section: Structure-activity Relationships Of Ziram-related Compounds mentioning
confidence: 90%
“…Ziram-treated SK-N-MC cells were washed with phosphate-buffered saline and then lysed in a thiol stabilizing buffer using the method of Jha et al (14). The samples were sonicated for 10 s, centrifuged for 15 min at 13,000 ϫ g, mixed with 2 parts thiol gel buffer (33 mM Tris-HCl, pH 6.8, 2.7 M urea, 2.5% sodium dodecyl sulfate, and 13% glycerol), and boiled for 2 min, and 10 g of protein/ lane was loaded on a 12% SDS-PAGE gel (15).…”
Section: Measurement Of 26 S Proteasome Activity and Cell Death In Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that cell death results from an interactive network of pathogenic factors in which no one component is essential and where the initiating pathogenic factor may vary in different individuals (figure 6). Indeed, laboratory studies demonstrate that oxidative stress can damage mitochondria and proteasomes, [152][153][154] mitochondrial dysfunction leads to oxidative stress and proteasomal damage, 155,156 and proteasomal dysfunction causes oxidative stress and mitochondrial dysfunction. 155,157,158 Furthermore, it has been shown that oxidative stress and proteasome inhibition act synergistically to promote protein misfolding.…”
Section: Introductionmentioning
confidence: 99%